2006
DOI: 10.1152/ajpcell.00573.2005
|View full text |Cite
|
Sign up to set email alerts
|

Aortic smooth muscle and endothelial plasma membrane Ca2+ pump isoforms are inhibited differently by the extracellular inhibitor caloxin 1b1

Abstract: Plasma membrane Ca(2+) pumps (PMCA) that expel Ca(2+) from cells are encoded by four genes (PMCA1-4). In this study, we show that aortic endothelium and smooth muscle differ in their PMCA isoform mRNA expression: endothelium expressed predominantly PMCA1, and smooth muscle expressed PMCA4 and a lower level of PMCA1. In this study, we report a novel peptide (caloxin 1b1, obtained by screening for binding to extracellular domain 1 of PMCA4), which inhibited PMCA extracellularly, selectively, and had a higher aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
75
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 50 publications
5
75
0
Order By: Relevance
“…In contrast, others have shown that mRNA for PMCA1 is more prevalent than that for PMCA4 in rat cultured aortic VSMCs, with PMCA4 transcripts suggested to be at only a quarter of the level of those for PMCA1 (Sasamura et al, 2002). In porcine aortic endothelial cells PMCA1 RNA has been shown to be detectable at a higher level than PMCA4 transcripts (Pande et al, 2006;Szewczyk et al, 2007). Thus, the vascular expression of PMCA1 and 4 may be species specific, with further work being required to clearly determine the relative expression of PMCA1 and PMCA4 in VSMCs and endothelial cells, particularly in resistance arteries.…”
Section: Expression Of Plasma Membrane Calcium Atpases In the Vasculamentioning
confidence: 88%
See 3 more Smart Citations
“…In contrast, others have shown that mRNA for PMCA1 is more prevalent than that for PMCA4 in rat cultured aortic VSMCs, with PMCA4 transcripts suggested to be at only a quarter of the level of those for PMCA1 (Sasamura et al, 2002). In porcine aortic endothelial cells PMCA1 RNA has been shown to be detectable at a higher level than PMCA4 transcripts (Pande et al, 2006;Szewczyk et al, 2007). Thus, the vascular expression of PMCA1 and 4 may be species specific, with further work being required to clearly determine the relative expression of PMCA1 and PMCA4 in VSMCs and endothelial cells, particularly in resistance arteries.…”
Section: Expression Of Plasma Membrane Calcium Atpases In the Vasculamentioning
confidence: 88%
“…However, Pande and colleagues have suggested that PMCA4 is the dominant form in pig aortic VSMCs (Pande et al, 2006). In contrast, others have shown that mRNA for PMCA1 is more prevalent than that for PMCA4 in rat cultured aortic VSMCs, with PMCA4 transcripts suggested to be at only a quarter of the level of those for PMCA1 (Sasamura et al, 2002).…”
Section: Expression Of Plasma Membrane Calcium Atpases In the Vasculamentioning
confidence: 98%
See 2 more Smart Citations
“…The use of human erythrocyte ghosts was common in the preparation of purified PMCA for this purpose (9). However, this will yield mainly PMCA4 as this is the main isoform expressed in human red blood cells.…”
mentioning
confidence: 99%